Department of Education Computerization Program (DCP): Its Effectiveness and Problems Encountered in School Personnel’s Computer Literacy - Mula, Richard S.; Bucar, Jimmy D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The DepEd Computerization Program (DCP) is a nationwide initiative to provide public elementary schools with computers and other ICT equipment to enhance the teaching and learning process. However, the effectiveness of this program and its impact on the computer literacy level of school personnel have yet to be fully explored. This study attempted to fill this gap by examining the perceptions of the school personnel of public elementary schools in the Bohol Division of the Department of Education about the DCP implementation and its relation to their computer literacy level and the problems they encountered in using the ICT equipment in the school year 2020–2021. The study also investigated the influence of the school personnel's profile on their computer literacy level and the problems they encountered. Results revealed that the DepEd Computerization Program (DCP) is highly effective, and the computer literacy of school personnel is very satisfactory. There is a significant relationship between the effectiveness of DCP and the problems encountered by school personnel. The computer literacy of school personnel is also significantly related to their years of teaching, specialized training attended, and age. The problems encountered by school personnel are significantly related to their age, gender, years of teaching, specialized training attended, IPCRF rating and DCP packages received. The study concludes that the implementation of DCP and the computer literacy of school personnel are congruent based on the data gathered, despite the problems encountered.